Household Time is a Scarce Resource: How does Time Allocation within the Household affect Children's Schooling Performance? - Beltrán, Arlette (2013)
This paper measures the impact of time distribution of parents and children over the students’ age-grade retardation. The research uses the Time Use Survey applied in Peru in 2010 and cross-sectional econometric models. The results point out that the time mothers dedicate to educational issues influences significantly when children are at primary school, while the time spent by the father is important to children between 12 and 17 years old. In any case parents’ education is important. The time children spend studying is also important for school performance; it competes against child labor outside or inside of the home.